(untitled) (Fiep Bulletin - online, 2013)
Currently, volleyball is working in several ways, a factor which depends on the location, the public, and, though the goals that it aims to achieve with this practice. Thus, this research was to examine how the main focus content volleyball has been working with the 5th grade State College of Campo Mourao - PR and the teacher is responsible for this, is used only for Fitness Traditional or expands its content the conceptual dimensions, procedural and atitudinal, there was a need for both to consider whether the way it treated the way volleyball helps students learn to relate to colleagues; investigate whether there was adapted materials, and local rules of practice during the lessons and identify the difficulties encountered by Professor of Physical Education to work if the content volleyball with the children of the 5th series. This research was characterized as descriptive, and the sample of a teacher who was Minister of Physical Education classes for all 5th grade elementary school of the College Estadual de Campo Mourao - PR. The instruments used for data collection were: systematic observation with specific plug and record in a questionnaire, which is applied to the end of the research professor of Physical Education participating in the research. From the collection of these data were analyzed in a qualitative analysis by means of content for the questionnaire, and quantitative analysis, by percentage for the systematic observation of chips. It is therefore concluded that the content volleyball was working adequately to school, seeking basic knowledge of this modality, but respecting the characteristics of age, and worked with all aspects of content, using most of the time of mixed method and thus making it had the participation of all pupils in class.